2015 IEEE World Haptics Conference (WHC) 2015
DOI: 10.1109/whc.2015.7177687
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary design of a multi-touch ultrasonic tactile stimulator

Abstract: International audience— This paper presents a method to control ultrasonic waves on a beam, allowing to obtain a Multi-touch ultrasonic tactile stimulation in two points, to give the sensation to two fingers, from two piezoelectric transducers. The multi-modal approach and the vector control method are used to regulate the vibration amplitude, in order to modulate the friction coefficient with the fingers. An analytical modelling is presented, with experimental validation. Finally a psychophysical experiment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In [9] we have shown that the friction at P 1 (resp. P 2 ) is a function of W 1 (resp.W 2 ) at the condition that the wavelength of the two mode shapes is high enough to produce very different friction reduction felt by a user moving one finger at the nodes and antinodes of vibration.…”
Section: Design Of the Prototypementioning
confidence: 87%
See 1 more Smart Citation
“…In [9] we have shown that the friction at P 1 (resp. P 2 ) is a function of W 1 (resp.W 2 ) at the condition that the wavelength of the two mode shapes is high enough to produce very different friction reduction felt by a user moving one finger at the nodes and antinodes of vibration.…”
Section: Design Of the Prototypementioning
confidence: 87%
“…The authors presented 4 different tactile maps, but they also point out that the method has the disadvantage to produce audible christophe.giraud-audine@ensam.eu noise by principle. In [9], [10], we presented a multimodal approach which allows a programmable tactile stimulation on two fingers located on two independent positions, on a 1D device. It consists in using two vibration modes which are energized at the same frequency, and which are superimposed in order to control the vibration amplitude at the positions of two fingers.…”
Section: Introductionmentioning
confidence: 99%
“…If a stationary wave would have been set on the beam, then the users would have felt nodes and antinodes of vibration successively on each fingers, and would not have detected a finger smoother than the other [4]. Moreover, 5 subjects found the beam more slippery for the left finger compared to the beam without any vibration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they do not allow to precisely control the vibration amplitudes at two or more different positions simultaneously. To cope with this issue, [4] proposed to superimpose two vibration modes, and to control the vibration amplitude of each mode according to the position of two fingertips. This principle take advantages of modal superimposition by using two modes which half wavelength is higher than 12 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Phased actuator array can focus ultrasounds to create localized mid-air sensations [9]. Modal synthesis combines vibration modes of the surface to vibrate chosen locations while cancelling others [10], [11]. All those techniques operate remotely from actuators, in their far field where diffraction limits the resolution to the wavelength scale.…”
Section: Introductionmentioning
confidence: 99%